Empowering upland farmers to become more resilient towards climate change – experiences from Toraja, Indonesia. (February 2019) - Iswoyo, H; Stoeber, S; Kaimuddin,; Yassi, A; Dermawan, R; Ramba, T
Abstract: Climate change is a factual phenomenon which is currently occurring and has affected every part of the world. It is disastrous in agriculture as in long term the harvest failure and diminishing farmland could result in food shortage hence world crisis. Farmers are most susceptible, therefor helping them to prepare, adapt and mitigate the impact of climate change become essential. This paper presents the factual climate-related problems in agriculture. It also shows stages of activity conducted by collaboration of farmers, university and NGO in stimulating and empowering farmers to be more aware, ready, smart and capable in proposing efforts of adaptation for their farms. The process acknowledged that farmers are also curious for field experiment before a technology can be fully adopted by them.